The Authority of the Financial Services Authority Regarding the Application for Postponement of Debt Payment Obligations for Insurance Companies in the Legal Certainty and Justice Perspective - Manurung, Novio (Universitas Pelita Harapan, 2025)
From a normative juridical perspective, the Financial Services Authority (OJK) grants the authority to apply for Postponement of Debt Payment Obligations (PKPU). On the basis of this authority, OJK has never given approval to creditors to apply for PKPU against debtor insurance companies. The research results show that normatively the space for creditors to apply for PKPU against insurance companies is closed and not possible. The Panel of Judges in PKPU Decision Number 389/Pdt.Sus-PKPU/2020/PN-Niaga.Jkt.Pst. applied the law as form of social control and social engineering. There is a need to update the PKPU application procedure which can be submitted by creditors. The main issues include the provisions regarding the bankruptcy application procedure in Law Number 40 of 2014 on Insurance apply mutatis mutandis to PKPU applications; Bankruptcy application procedures in OJK Regulation Number 28/POJK.05/2015 applies mutatis mutandis to applications PKPU; Addition of phrases to Article 2 paragraph (5) Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, namely